Diary of a wimpy kid : dog days - Kinney, Jeff. (New York : Amulet Books, 2009)
Greg Heffley recounts his daily experiences during summer vacation as he tries to live out his ultimate fantasy of spending the days indoors playing video games with no responsibilities and no rules, despite his mother's attempts to pack the summer with outdoor activities and family fun.
Booklist.
Horn Book.
Pub Weekly.
Booklist, October 2009.
Horn Book, October 2010.
Pub Weekly, October 2009.
Keywords: Diaries -- Juvenile fiction; Summer -- Juvenile fiction; Diaries -- Fiction; Humorous stories; Summer -- Fiction; Diaries -- Fiction; Humorous fiction; Summer -- Fiction; Humorous fiction